Gut microbiota implication in diabetic kidney disease: mechanisms and novel therapeutic strategies - Yujie Zhang; Jianbo Qing; Yasin Abdi Saed; Yafeng Li (Renal Failure, 2025)
Diabetic kidney disease (DKD) is one of the leading causes of chronic kidney disease and end-stage renal disease worldwide, predominantly driven by the rise in type 2 diabetes mellitus. Recent evidence highlights the crucial role of gut microbiota dysbiosis in the development and progression of DKD. Dysbiosis, characterized by a reduction in beneficial short-chain fatty acid-producing bacteria and an increase in pathogenic species such as Proteobacteria and Bacteroides, exacerbates systemic inflammation, insulin resistance, and kidney damage through mechanisms like increased intestinal permeability and the production of pro-inflammatory metabolites like lipopolysaccharides. This review explores the impact of specific bacterial taxa on DKD risk and progression, such as Alistipes, Subdoligranulum, and their interactions with metabolic pathways. Furthermore, we discuss novel therapeutic strategies targeting gut microbiota, including probiotics, prebiotics, synbiotics, and fecal microbiota transplantation, which have shown promise in ameliorating DKD symptoms. However, the heterogeneity of gut microbiota across individuals and the challenges in treatment standardization call for personalized approaches and further research into the gut-kidney axis.